2018
DOI: 10.21037/cco.2018.07.06
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of soft tissue sarcomas

Abstract: Soft tissue sarcomas are rare and a heterogeneous group of neoplasms. Over the years imaging has played a crucial role in the initial staging, monitoring response to chemotherapy, and surveillance for recurrence. In the era of rapidly evolving individualized treatment due to evolving chemotherapies, increasing demand has been placed on the role of imaging in the management of this heterogeneous group. The rapidly evolving technologies in imaging are trying to keep up with the challenge, with development of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 97 publications
(147 reference statements)
0
34
0
24
Order By: Relevance
“…Patel et al showed that a discrete elevated Cho-peak could diagnose malignancy with a sensitivity and specificity of 88 % and 68 %, respectively. In comparison, a low concentration (< 0.3 mmol/kg) has a negative predictive value of 100 % for excluding malignancy [6]. In our opinion, the limitation and the most probable reason this method has not yet been implemented in standard practice is that it is technically challenging and has potential pitfalls.…”
Section: Soft-tissue Sarcomasmentioning
confidence: 93%
See 2 more Smart Citations
“…Patel et al showed that a discrete elevated Cho-peak could diagnose malignancy with a sensitivity and specificity of 88 % and 68 %, respectively. In comparison, a low concentration (< 0.3 mmol/kg) has a negative predictive value of 100 % for excluding malignancy [6]. In our opinion, the limitation and the most probable reason this method has not yet been implemented in standard practice is that it is technically challenging and has potential pitfalls.…”
Section: Soft-tissue Sarcomasmentioning
confidence: 93%
“…MRI provides excellent characterization of tissues and enables adequate evaluation of local tumor extent, which is crucial for delineating safe surgical margins. Regarding the signal characteristics of lesions, Patel divides all softtissue masses into four categories (see ▶ Table 4) [6].…”
Section: Soft-tissue Sarcomasmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 In soft tissue tumors, radiographs allow the detection and definition of the mineraliza-tion pattern of a lesion, aiding the diagnosis/differential diagnosis with other tumors or pseudotumoral lesions (ossifying myositis, tumor calcinosis, vascular malformations, gout, extraskeletal mesenchymal chondrosarcoma, extraskeletal osteosarcoma, liposarcoma and synovial sarcoma); in addition, they reveal valuable information on tumor density (adipocytic tumors) and possible underlying bone involvement. 14,16 In view of a bone or soft tissue lesion with clinical and radiographic characteristics denoting biological aggressiveness, additional imaging tests are required 12 to determine local extension, distant spread (metastases) and histological diagnosis (►Figure 1).…”
Section: Role Of Imaging and Pathology In Evaluating Bone And Soft Timentioning
confidence: 99%
“…Later studies confirmed its value in Ewing sarcoma staging 28 and, to date, the MSC recommends that the size of nine centimeters is the best prognostic indicator for osteosarcoma. The addition of the T3 designation for skip metastasis 9,16 was another modification -Wuisman et al 29 compared 224 patients without skip metastasis at diagnosis with 23 patients who presented such lesions. Twenty two of these 23 individuals had local recurrence or distant metastasis and died; adjuvant chemotherapy did not improve their prognosis.…”
Section: Primary Malignant Bone Tumors Staging (Ajcc)mentioning
confidence: 99%